Understorey Plant Diversity in Imbo Putui Customary Forest, Kampar Regency, Riau - Syaiful Syifa; Pebriandi Pebriandi; Viny Volcherina Darlis (Jurnal Biologi Tropis, 2026)
The Imbo Putui Customary Forest is an ecosystem that plays an important ecological role as a provider of environmental services and habitat for tropical biodiversity. This study analyzes the diversity of understory plants in the Imbo Putui Customary Forest using a descriptive quantitative research design. Data collection was carried out using a 100 × 20 m main plot combined with 2 × 2 m subplots as sampling units for understory vegetation. The results of this study show that there are 29 plant species belonging to 18 families, originating from 4 habits: herbaceous, shrub, grass, and shrub, and three families were found to be abundant, namely Poaceae, Arecaceae, and Asteraceae. The results showed that the understory plant community consisted of various growth forms, with herbaceous plants showing the highest level of diversity, while shrubs showed the lowest level of diversity. Overall, the level of diversity indicates that the forest ecosystem is in relatively good ecological condition. These findings confirm the ecological stability of the Imbo Putui Customary Forest and emphasize the importance of sustainable conservation and management efforts to maintain ecosystem balance and provide benefits to indigenous communities.